Fungi associated with senescent leaves of Lumnitzera racemosa Willd. in taklong Island, Guimaras. - Luna, Dexter Bryan Padlan
Fungi play a vital role in our ecosystem and of utmost important to man. Despite these, fungi have received little attention in discussions on global biodiversity. Among the natural habitats and hosts of fungi, mangroves belong to one of the poorly developed and rapidly disappearing ecosystems., In the Philippines, reports on manglicolous fungi are few. Moreover, mycota on senescent of Lumnitzera racemosa Willd. have never been studied. This study was undertaken (1) to describe, classify and identify fungi associated with senescent of Lumnitzera racemosa willd. in Taklong Island, Guimaras; (2) to determine the abundance and occurrence of fungi on this host; and (3) to contribute fungal isolates to the culture collection of the Division of Biological Sciences Laboratory in view of the Biodiversity Program. Senescent of Lumnitzera racemosa Willd. were collected in Taklong Island, Guimaras. The method of incubation by Leach (1961-1963) in the near ultraviolet chamber to induce sporulation was followed. Examination and identification of fungi were done with the aid of Keys for Identification. Data gathered were analyzed based on the frequency of occurrence. The results showed that 10 Deuteromycetes and 1 Ascomycete were identified from the senescent of Lumnitzera racemosa Willd. The very frequently occuring species were Coelomycete sp. 1 (31.64) and Ascomycete sp. 1 (30.47). Asperigillus sp. (24.61), Penicillium sp. (22.66), Nigropora sp. (20.31), Coelomycete sp. 2(17.97), Rhizopus sp. (15.23) and Paecilomyces sp. (10.55) were the frequently occuring species. The infrequent species were Coelomycete sp. 3 (6.25), Alternaria tenuissima (4.30) and Curvularia lunata (2.73) and Curvularia lunata (2.73) The occurrence and development of fungi on the leaf samples could be accounted for by a number of factors such as habitat and nature of substrate.